DAMPAK SERTIFIKASI KOMPETENSI TERHADAP EFEKTIVITAS KERJA SDM MICE - Yuli Setiawati; Liza Khairunnisa Gultom (POLITEKNIK LP3I JAKARTA, 2025)
The development of the MICE (Meeting, Incentive, Conference, and Exhibition) industry in Indonesia has shown a positive trend in the post-COVID-19 era. The government and industry stakeholders continue to formulate various strategies to strengthen the role of this sector in national tourism and economic growth. One of the key strategies is enhancing the quality of Human Resources (HR) through competency certification, aiming to address global challenges and increase the competitiveness of the industry. Competency certification is considered a crucial instrument to ensure professionalism, expertise, and formal recognition of the skills possessed by HR in the MICE sector. This study aims to analyze the impact of competency certification on the work effectiveness of HR in the MICE industry, particularly in terms of productivity and performance. The research employs a descriptive qualitative approach, with data collected through in-depth interviews and literature studies. The findings indicate that competency certification has a positive impact on improving HR work effectiveness in the MICE sector, including aspects of work productivity, service quality, and adaptability to industry dynamics. Therefore, certification not only serves as a validation of expertise but also acts as a catalyst for overall performance improvement within the MICE industry ecosystem.